(3eHGQb GdCRgGQ aj TQM eTGQb GdCfhGQs - (3YHO GddWja Hf YHO GdYRjR Hf Cejf GdOjf Hf aQTJG GdcQeGfj, GdeYQha HGHf edc,J (B801 (3g` s; (3GdMSf Hf eMeO Hf GdMSf Hf MjOQ GdYOhj GdYeQj GdUGZGfj GdMfaj QVqj GdOjf,J (B650 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi gOjI GdgOGjI hGdESdGe , hYWjI GdOQGjI hGdEYdGe , hHYO jbhd heeG Ufa ajg (B( (3jQjO Yde GdMOjK (B) (3ef GdcJH GdaGNQI hGdRHO GdhGaQg cJGH eTGQb GdCfhGQ ai UMjM GdCNHGQ hcGfJ dg TQhM , HYVgG HSjW s
(3BNQgG (B:s
(3e (B( (3eSde (B) : (3YHO Gddg Hf GdRHjQ Hf GdYhGe Qhi eSde Yfg (B: (3dG Zdg ZdG Gddg hMOg dGTQjc dg , dg Gdedc hdg GdMeO GHf YeQ EJabG Ydi GdQhGjI Yfg (B: (3dHjc Gddge dHjc Gddg CYde HGdUhGH hBNQ OYhGfG Cf GdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV YHGQGJgG HGdMeQIs
(3MhGagG eJBcdIs
(3fSNI bOjeI s
(3cJHJH HNWhW eNJdaI s
Keywords: (3GdMOjK h GdeUWdMs